2010
DOI: 10.1167/iovs.09-4881
|View full text |Cite
|
Sign up to set email alerts
|

Macular Pigment Optical Density in Central Serous Chorioretinopathy

Abstract: MPOD may decrease in eyes with chronic CSC and in the fellow eyes. Low MPOD may indicate a risk of chronic CSC, and a decrease in MPOD may be accelerated by thinning of the central retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Two masked orthoptists who used the same testing device and protocol performed all measurements. Before the study, the reliability of the measurements between the two orthoptists was confirmed as reported previously [15].…”
Section: Measurement Of the Mpod Levelmentioning
confidence: 65%
See 2 more Smart Citations
“…Two masked orthoptists who used the same testing device and protocol performed all measurements. Before the study, the reliability of the measurements between the two orthoptists was confirmed as reported previously [15].…”
Section: Measurement Of the Mpod Levelmentioning
confidence: 65%
“…Considering the normal data that we previously reported, we found that 39 eyes were needed to detect a change in the MPOD optical density of 0.10 density units (DUs) [15]. Because we expected dropout during the follow-up period, we enrolled 43 consecutive Japanese subjects over 40 years old who had never taken supplementation previously.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of ethnic comparisons and white subject-dominated MP studies, there have been a few MP investigations with East Asian participants, [49][50][51][52] and one with South Asian participants. 53 The aims of the current study were firstly to assess MPOD in a healthy group of young adults of South Asian origin.…”
mentioning
confidence: 99%
“…Ahlers et al demonstrated diffuse hyper-re- SIM -superior inferior macula; SOM -superior outer macula; NIM -nasal inferior macula; NOM -nasal outer macula; IIM -inferior inner macula; IOM -inferior outer macula; TIM -temporal inferior macula; TOM -temporal outer macula fibre layer could also have an influence on the hyper-reflectivity of the outer plexiform layer as observed in SD-OCT by minimising the amount of scattered light; the light backscatter from the Henle fibres could then be better detectable. Macular pigment has been noted to be released from the Henle fibre layer and inner plexiform layer in patients with both acute and chronic CSC [7]. Further studies to evaluate the potential role of macular pigment of the hyper-reflectivity of the OPL are warranted.…”
Section: Discussionmentioning
confidence: 99%